2018
DOI: 10.7554/elife.40179
|View full text |Cite
|
Sign up to set email alerts
|

Unique morphogenetic signatures define mammalian neck muscles and associated connective tissues

Abstract: In vertebrates, head and trunk muscles develop from different mesodermal populations and are regulated by distinct genetic networks. Neck muscles at the head-trunk interface remain poorly defined due to their complex morphogenesis and dual mesodermal origins. Here, we use genetically modified mice to establish a 3D model that integrates regulatory genes, cell populations and morphogenetic events that define this transition zone. We show that the evolutionary conserved cucullaris-derived muscles originate from … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
110
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 70 publications
(115 citation statements)
references
References 97 publications
3
110
0
2
Order By: Relevance
“…However, it is important to note that the muscles connecting the pectoral appendage and the head are always attached to the pectoral girdle, not the pectoral fin. This also applies to one of the other strongest lines of evidence supporting Gegenbaur's theory: the fact that in at least some vertebrates, such as mice, neural crests—which are mainly involved in skeleton formation and muscle/tendon attachments in the head but not the trunk—contribute to not only the formation of some parts of the pectoral girdle 53,68,72 but also at least partially to the attachment of tendons/muscles connecting it to the head 24,71 . That is, the neural crest cell contribution to formation of the pectoral appendage skeleton, as well as to its attachments to the head, seem to apply only to the pectoral girdle, not to the pectoral fin.…”
Section: Support For Fin‐fold Theory Vs For Gegenbaur's Theorymentioning
confidence: 88%
See 1 more Smart Citation
“…However, it is important to note that the muscles connecting the pectoral appendage and the head are always attached to the pectoral girdle, not the pectoral fin. This also applies to one of the other strongest lines of evidence supporting Gegenbaur's theory: the fact that in at least some vertebrates, such as mice, neural crests—which are mainly involved in skeleton formation and muscle/tendon attachments in the head but not the trunk—contribute to not only the formation of some parts of the pectoral girdle 53,68,72 but also at least partially to the attachment of tendons/muscles connecting it to the head 24,71 . That is, the neural crest cell contribution to formation of the pectoral appendage skeleton, as well as to its attachments to the head, seem to apply only to the pectoral girdle, not to the pectoral fin.…”
Section: Support For Fin‐fold Theory Vs For Gegenbaur's Theorymentioning
confidence: 88%
“…Moreover, recent developmental studies have shown that the cucullaris and its derivatives (eg, protector pectoralis, trapezius/sternocleidomastoideus), which are key muscles connecting the head and pectoral girdle in early gnathostome fossils such as placoderms 69 as well as living gnathostomes, 18 are actually head, and namely branchial, muscles that are part of the cardiopharyngeal field 19,24,70,71 . In fact, these are not the only head muscles that are developmentally part of the branchial muscle and that connect the pectoral girdle to the branchial arches: there are various other branchial muscles that do so, such as the constrictores branchiales and the coracobrachiales 30,31 .…”
Section: Support For Fin‐fold Theory Vs For Gegenbaur's Theorymentioning
confidence: 99%
“…The phenotype of Patient 4 included early developmental delay and lactic acidosis in common with Patients 1 and 2b, but he also had reversible infantile-onset myopathy which has not previously been reported in association with LARS2 variants. Interestingly, the myopathy was most severe in the neck muscles, which are derived from a different lineage and regulated by distinct genetic programs compared to other muscle types (e.g., quadriceps; Heude et al, 2018). The unusual features of this patient may be related to the combination of LARS2 missense variants, one of which has reduced aminoacylation efficiency at low ATP concentrations, or could be a result of genetic and/or environmental factors.…”
Section: Discussionmentioning
confidence: 89%
“…6 The same ectodermal connective tissue merges, in part, with connective tissue of mesodermal origin and forms the musculature of the trapezius (anterior portion) and of the sternocleidomastoid (cleidomastoid portion) muscles. 20,21 The final functional unit that is skeletal muscle thus possesses different embryological origins. Body fluids such as blood and lymph have a mesodermal origin, while cerebrospinal fluid (CSF) has an ectodermal origin.…”
Section: Reflections On Fascial Tissuementioning
confidence: 99%
“…From an embryological point of view this term is correct, because at the level of the skull the musculature and connective tissues derive from the ectoderm. 6,7 From the anatomical and functional point of view, such a description is inaccurate. The terms superficial and deep are used to delimit the layers of fascial tissue within the limbs.…”
Section: Introductionmentioning
confidence: 99%